Proceedings of the 16th International Symposium on Power Semiconductor Devices &Amp;amp; IC's 2004
DOI: 10.1109/wct.2004.240217
|View full text |Cite
|
Sign up to set email alerts
|

A high breakdown voltage IC with lateral power device based on SODI structure

Abstract: Absrract: A high-performance power technology has been developed in which conventional SO1 lateral power device is merged with novel thick film technology in backside of its substrate, such as Silicon 00 Double Insulator (SODI) structure. In addition to realize a high breakdown voltage performance with the assumption of 1.2kV class application, SODI structure has mainly two advantages.One is a low cost-performance of the initial SO1 substrate can be done, because a design of initial buried oxidation layer thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The thickness of the silicon oxide layer must be increased to decrease leakage current in electrical isolation regions. 9,10) Thus, the BOX layer must be thicker than the currently available SOI wafers. In general, a BOX layer is formed by thermal oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the silicon oxide layer must be increased to decrease leakage current in electrical isolation regions. 9,10) Thus, the BOX layer must be thicker than the currently available SOI wafers. In general, a BOX layer is formed by thermal oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The self-isolation technique is more cost effective than the junction isolation [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and dielectric isolation techniques. [23][24][25][26][27][28][29][30] This is because it uses a lessexpensive silicon wafer that is uniformly doped, and it does not need special process steps such as deep diffusion layer and trench formations for the isolation process.…”
Section: Device Conceptmentioning
confidence: 99%
“…5) Akiyama et al reported that the higher BV of 1050 V was achieved in his lateral diode fabricated in silicon-on-double-insulator (SODI) structure, which was formed by backside silicon etching of SOI wafer followed by dielectric layer deposition and metal electrode formation. 6) Endo et al reported that his lateral insulated gate bipolar transistor (LIGBT) with SRFP fabricated in SOI with 2-m-thick BOX achieved good characteristics not only in the high BV of 580 V, but also in the fast switching of 280 ns. 7) However, there are no reports that a SOI micro-inverter IC achieved a higher BV than 700 V and a larger current capability than 3 A simultaneously.…”
Section: Introductionmentioning
confidence: 99%